First nationwide survey on cardiovascular risk factors in Grand-Duchy of Luxembourg (ORISCAV-LUX) - Alkerwi Ala'a; Sauvageot Nicolas; Donneau Anne-Françoise; Lair Marie-Lise; Couffignal Sophie; Beissel Jean; Delagardelle Charles; Wagener Yolande; Albert Adelin; Guillaume Michèle (BMC, 2010)
Abstract Background The ORISCAV-LUX study is the first baseline survey of an on-going cardiovascular health monitoring programme in Grand-Duchy of Luxembourg. The main objectives of the present manuscript were 1) to describe the study design and conduct, and 2) to present the salient outcomes of the study, in particular the prevalence of the potentially modifiable and treatable cardiovascular disease risk factors in the adult population residing in Luxembourg. Method ORISCAV-LUX is a cross-sectional study based on a random sample of 4496 subjects, stratified by gender, age categories and district, drawn from the national insurance registry of 18-69 years aged Luxembourg residents, assuming a response rate of 30% and a proportion of 5% of institutionalized subjects in each stratum. The cardiovascular health status was assessed by means of a self-administered questionnaire, clinical and anthropometric measures, as well as by blood, urine and hair examinations. The potentially modifiable and treatable risk factors studied included smoking, hypertension, dyslipidemia, diabetes mellitus, and obesity. Both univariate and multivariate statistical analyses used weighted methods to account for the stratified sampling scheme. Results A total of 1432 subjects took part in the survey, yielding a participation rate of 32.2%. This figure is higher than the minimal sample size of 1285 subjects as estimated by power calculation. The most predominant cardiovascular risk factors were dyslipidemia (69.9%), hypertension (34.5%), smoking (22.3%), and obesity (20.9%), while diabetes amounted 4.4%. All prevalence rates increased with age (except smoking) with marked gender differences (except diabetes). There was a significant difference in the prevalence of hypertension and of lipid disorders by geographic region of birth. The proportion of subjects cumulating two or more cardiovascular risk factors increased remarkably with age and was more predominant in men than in women (P<0.0001). Only 14.7% of men and 23.1% of women were free of any cardiovascular risk factor. High prevalence of non-treated CVRF, notably for hypertension and dyslipidemia, were observed in the study population. Conclusion The population-based ORISCAV-LUX survey revealed a high prevalence of potentially modifiable and treatable cardiovascular risk factors among apparently healthy subjects; significant gender and age-specific differences were seen not only for single but also for combined risk factors. From a public health perspective, these preliminary findings stress the urgent need for early routine health examinations, preventive interventions and lifestyle behavioural changes, even in young asymptomatic adults, to decrease cardiovascular morbidity and mortality in Luxembourg.